Analisis Pengaruh Hak Cuti, Pemberdayaan Karyawan, Dan Stres Kerja Terhadap Produktivitas Karyawan PT Zieka Putra Utama - Andriani, Desika; Apriyanto, Arif Nur (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2024)
This research aims to determine the analysis of the influence of leave rights, employee empowerment and work stress on employee productivity at PT Zieka Putra Utama, both partially and simultaneously. The data used in this research includes testing the validity of the variables Leave Rights, Employee Empowerment, and Work Stress on Employee Productivity where the calculated r is greater than the table r of 0.2542. From the results of the reliability test using the Cronbach Alpha formula, there are results with r alpha values ​​> 0.6, namely r alpha Leave Rights (0.869), Employee Empowerment (0.829), Work Stress (0.822), Employee Productivity (0.884). The results of multiple linear regression analysis in this research are Y = 2.476 + 0.311 (X1) + 0.311 (X2) + 0.316 (X3) while the coefficient of determination (R²) is 0.645 or 64.5%, which means that Leave Rights, Employee Empowerment, and Job Stress on Employee Productivity explains the variation in Employee Productivity by 64.5%. The t test and F test show a significant effect both partially and simultaneously with the t test results from Leave Rights t calculated greater than t table (3.003>2.00324) from Employee Empowerment t calculated greater than t table (2.956>2, 00324), from Job Stress the calculated t is greater than the t table (2.258>2.00324) while the F test shows the calculated F value is 36.801 > F table 2.77 with a significance level of 0.000 < 0.05, so Ho is rejected and Ha is accepted . So it can be concluded that the variables: Leave Rights, Employee Empowerment, and Work Stress, Employee Productivity at PT Zieka Putra Utama have a positive and significant effect on Employee Productivity, both partially and simultaneously.